Prosthetic Need between Different Age and Gender ‎With Patient Attending College of Dentistry,Tikrit ‎University (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Background: the most important factor that affects speak, mastication and aesthetics is tooth loss which in turn imitated on the quality of life. The goal of our research was to evaluate the prosthetic need in sample attending prosthetic department and compare between age and gender.Material and methods: A sample of 244 patients was randomly chosen for questionnaire in the (Removable Prosthodontics Clinic) into College of Dentistry-Tikrit University. All subjects were divided in six groups according to their age and also divided according to gender. Intraoral examinations were performed and reasons for extraction were recorded. All statistic calculations were performed using SPSS 23 (Statistical Package for Social Sciences).Results: The total number of 244 patients was involved in this study: 165 (67.6%) males and 79 (32.4%) females. We found that the higher percentage of patients were in the age group of (20-29) for males which was (23%, 56 patient), while the higher female percentage was found in the age group of (40-49) which was 11.5% . Reasons for extraction recorded the higher percentage due to Caries for both males (75.2%) & females (81 %) as suspected.Conclusion:The number of patient attending prosthetic department male more than female. Dental caries were the principal cause for extractions in younger patients followed by periodontitis. Society needs more motivation about dental health and care.